Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
The solution to log(x) base e = 3 is x = e^3.
To solve this equation, we need to understand that log(x) base e is the same as ln(x), where ln represents the natural logarithm. Therefore, we can rewrite the equation as ln(x) = 3.
To isolate x, we need to exponentiate both sides of the equation with e, which is the base of the natural logarithm. This gives us:
e^(ln(x)) = e^3
Using the property of logarithms that states e^(ln(x)) = x, we can simplify the left-hand side of the equation to get:
x = e^3
Therefore, the solution to log(x) base e = 3 is x = e^3.
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.